Pengaruh Kompetensi, Independensi, Etika Auditor, Time Budget Pressure Dan Due Professional Care Terhadap Kualitas Audit( Studi Empiris pada Kantor Akuntan Publik di Jawa Tengah dan DIY ) - Wamuznia, Wamuznia, Drs. Muhammad Abdul Aris, M.Si (2016)
The purpose of the study was to analyze the effect of the competence, independence, ethics auditors, time budget pressure and due professional care, especially at the internal audittors working in public accounting in Central Java and Yogyakarta. The population this study are all auditors who work in public accounting in Central Java and Yogyakarta. The sampling technique used was convinience sampling method, with the acquesition of a sample of 69 respondents. The primary data collection using the questionnaire. The data are analyzed using multiple linier regression analysis. The result of the analysis proved that the variable competence, independence, ethics auditors, time budget pressure have significant effect on audit quality, while due professional care didn't have significant effect on audit quality. Keywords: competence, independence, ethics auditors, time budget pressure, due professional care and audit quality.